TI_GERICHTE 16.2020.21 vom 17. Juni 2021 , Contratto d'appalto: garanzia per difetti - onere di allegazione - TI Tribunale d'appello (2021)
Contratto d'appalto: garanzia per difetti - onere di allegazione